Effect of Zinc Phosphating and Adhesive Thickness on Delamination Bonding Strength for Rubber/Steel Laminate Composite - Guntur Tri Setiadanu; Mutiara Pangestika Gunarso; Widhiatmaka . (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Rubber/steel laminate composite is widely used for Rubber Vibration Insulator (RVI), part of the diesel power plant engine. This study aims to determine the effect of phosphating process and the thickness of the adhesive bonding into delamination resistance of rubber/steel laminate composite. After shot blasting process, some substrates are coated with zinc phosphate and other substrates are remain uncoated. Variations of the thickness of primer adhesive are 2.7, 6.8 and 11.9 μm combined with variations of topcoat adhesive thickness are 2.4, 7.1 and 12.5 μm. The process of forming the laminate composite occurs through transfer molding process at 160C in 450 seconds. The laminate composite that has been formed then tested by peel-off test to determine the strength of delamination. Delamination surface was characterized by SEM-EDX. The results showed that zinc phosphating process on substrate effectively to increase the bonding strength of laminate composite due to the metal zinc phosphate formation and impurities cleanliness. The optimum thickness of adhesive primer achieved in 6.8 μm combined with 7.1 μm topcoat adhesive thickness, which bonding strength was reached 252.2 N.